The who, what and how of the current research at the Brazilian Symposium on Software Engineering - Cerqueira, Lidiany; Silva, Júlio César Andrade; Alvim, Ícaro Vasconcelos; Mendonça, Manoel; Santos, José Amancio Macedo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Software engineering is a socio-technical activity, and while many contributions focus on technical aspects, its research should benefit human stakeholders. The Who-What-How framework aims to capture the head beneficiary of a research study (the who), the predominant type of research contribution produced (the what), and the research strategies used in a study (the how), evaluating how these studies address the human aspects. This paper performs a replication study of “The who, what, how of software engineering research: a socio-technical framework” [50], which addressed the question of how papers from the ICSE and EMSE considered human aspects. This study uses the Who-What-How framework to analyze works published at the Brazilian Symposium on Software Engineering between 2019 and 2021. We analyzed 90 papers and found a significant amount of work that claims to benefit human stakeholders, most presented descriptive contributions and adopted the Respondent research strategy. Triangulation of research was low, as only 15 papers reported using mixed strategies.